Validation of modified COVID-19 Phobia Scale (MC19P-SE) to examine the relationships between corona anxiety and COVID-19 symptoms: A case-control study - Luthful Alahi Kawsar; Syed Toukir Ahmed Noor; Md. Atiqul Islam; Mohammad Romel Bhuia (Journal of Mood and Anxiety Disorders)
Purpose: The main purpose of the present study is to validate the modified COVID-19 phobia scale (MC19P-SE) in Bangla and use it to identify the link between COVID-related anxiety and the onset of COVID-19 symptoms. Methods: A retrospective case-control study was conducted in Sylhet, a northeastern district in Bangladesh, focusing on a population of 18 years or older. The MC19P-SE scale was used to gather data on coronaphobia among the respondents, and factor analysis was used to derive reliable factors. We employed a multivariable logistic regression model to identify the relationships between coronavirus anxiety and COVID-19 symptoms. Results: Among the 482 participants, 42 % manifested COVID-19 symptoms. Factor analysis revealed four underlying factors: psychological anxiety, psychosomatic anxiety, economic anxiety, and social or excessive protective anxiety. MC19P-SE exhibited reliability with a Cronbach alpha coefficient of 0.91 for full-scale. According to the model, psychosomatic anxiety increased (AOR= 1.14, 95 % CI: 1.07, 1.22) the risk while social or excessive protective anxiety decreased (AOR=0.88, 95 % CI: 0.78, 0.99) the risk of developing COVID-19 symptoms significantly. Conclusion: The research found a significant relation in the Bangladeshi district of Sylhet between the onset of COVID-19 symptoms and anxiety associated with the virus. Furthermore, the findings affirm the potential reliability and validity of the MC19P-SE scale, strengthening its efficacy for future research and evaluations.